The analysis of legal regulation of palliative care in Ukraine - Kubarieva, Inna; Kotvitska, Alla; Beketova, Marharyta (ScienceRise: Pharmaceutical Science, 2017)
The aim of the study, resulting in the article, was to analyze the current state of legal regulation of palliative care in Ukraine. The scientific analysis methods, in particular, system analytical, content analysis, methods of generalization and grouping, were used in the present research. Results. The analyzed current WHO regulations during the research, allowed defining the strategic directions of development of palliative and hospice care at both national and international levels. Positive aspects of the current national legislation concerning palliative care were formulated. They include the definition of palliative care as a separate type of care, legislative confirmation of the terms "palliative care", "palliative treatment", "palliative patient", the use of a multidisciplinary approach to provide palliative care to HIV patients, implementation to the eighth issue of the State Drug Formulary (Appendix 8), and remedies for palliative and hospice care. The shortcomings of legislative acts regulating palliative care in Ukraine, in particular regulatory norms fragmentation, the absence of nosologies list for palliative care, in accordance with approved protocols of treatment, methods for calculating the need for medicines, the register of palliative patients, etc., were determined. The priority measures to improve the national legislation in the aspect of palliative care in Ukraine for the organizational, medical and pharmaceutical, social and pharmaceutical, as well as educational directions were offered. Conclusion. The prior purpose concerning the implementation of an effective model of palliative care in Ukraine is to form an adequate legal and regulatory framework, considering the multidisciplinary approach, WHO recommendations and the experience of the leading countries of the world. The "profile" law adoption with a clear definition of palliative care classification, medical, pharmaceutical, and social components of palliative care, sources, mechanisms and the amount of its financing is the basis of the mentioned changes